Attitudes toward English phonetics learning: a survey on Indonesian EFL learners - Sri Ayu Istiqomah; Alies Poetri Lintangsari; Widya Caterine Perdhani (Journal on English as a Foreign Language, 2021)
Indonesian EFL learners face challenges in comprehending English phonemes as it becomes one of the significant predictors of English literacy. Hence, the English Phonetics subject is considered one of the most difficult ones, making the teaching and learning process less effective. Addressing Indonesian EFL learners